Gonad maturation, larval growth and settlement of the slipper cupped oyster Crassostrea iredalei Faustino 1932 (Mollusca, Peleypoda: Ostreidei) - Abd Wahab, Nor Idayu (2017)
Crassostrea iredalei is a potential oyster species to be cultured in Malaysia intensively. By understanding factors that influence growth and survival of oysters from early development until spat stage will be useful in managing spat production in the hatchery. Therefore, this study has been assessed on gonadal stages, early development of larval, effect of cues on larval settlement, spat growth and capability of tolerance towards certain salinity and temperature. Research was mainly conducted at Fisheries Research Institute (FRI) Pulau Sayak, Kedah from June 2013 until June 2015. About 140 oysters were determined gonadal stages by biometric measurement and histology. For embryonic and larval development, 280 oysters were stripped-spawning and rearing by normal culture practice. Effects of stocking and algal density on larval development and survival also tested accordingly. Eye-spot larvae were tested for settlement and metamorphosis within 24 and 48 hour by four chemicals, γ-aminobutyric acid (GABA), isobutyl methylxanthin (IBMX), potassium chloride (KCl) and serotonin at different concentrations, microalgae (Chaetoceros calcitrans, Isochrysis galbana and Nannochloropsis sp.) and marine bacteria. Development of spat were observed and effects of short-term immersion in different salinity (10, 15, 20, 25 and 30 ppt) at fixed temperature 28±1oC and temperatures (15, 19, 23, 27, 31, 35oC) at fixed salinity 29±1 ppt) were determined in relation to growth, survival and clearance rate of spat. Histological results showed four gonadal stages were recognized viz. undifferentiated S1 where no sex cell developed, early development S2 where oocytes initiated, late development S3 where most oocytes developed to vitellogenic and mature S4 where follicles filled with postvitellogenic oocytes. Mature oysters indicated at shell length 73 to 83 mm and weight at 62 to 102 g. Sample of oysters dominated by late development stage S3 at 63 oyster and matured oysters were 31 female and 12 male. Complete planktonic stage of C. iredalei was recorded from day 12 to 16 where the early settled larvae was observed. Spatfall began on day 16 onwards. Mean specific growth rate (SGR) from day 2 until day 16 was recorded at 22.16% where growth rate at 14.64 μm day-1 in shell length and 18.60 μm day-1 in shell height. Linear relationship between shell length and shell height of larvae is given by an equation y= 1.2217x - 7.374, R2= 0.939 (n= 30). Larval rearing was recommended at 10 larvae mL-1 and algal density between 5 000 to 15 000 cells mL-1 for veliger larvae and increase up to 30 000 cells mL-1 in umbo stage. For larval settlement and metamorphosis, highest scored by bacterium identified as Bacillus cereus yielded up to 79% at cell density 103 after 48 hour significantly (p<0.05). It is proved that specific cues released by B. cereus able to induce high settlement rate within a short period. While only C. calcitrans at cell density 105 cells mL-1 induced larval settlement at 55% compared to I. galbana and Nannochloropsis sp. due to presences of eicosapentaenoic acid (EPA) and arachidonic acid (ARA) at high level has correlated with the ability of larvae to undergo settlement. All chemicals showed lower larval settlement in all concentration tested at 15% to 17% and only GABA was induced until metamorphosis at 28%. For IBMX and serotonin it is not recommended for C. iredalei due to expensive price compared to KCl but all of these chemicals has failed to induce settlement in high percentage within a short period. Larval survival were greater than 50% in all treatments excepted for bacterium C4 and chemicals concentration at 10-3 to 10-4 M onwards. Then, development of pediveliger larvae were observed until spat stage on day 16 onwards. The spats growth measured by shell length increased from day 5 (0.55±0.08 mm), 30 (6.06±0.98 mm) and day 60 (7.91±0.69 mm). Presence of epibiotic polychaete identified under family Spionidae. While effects of short-term immersion of spat at size 6-7 mm showed salinity at 25 ppt resulted high SGR at 18% and clearance rate at 11.14x103 cells mL-1 ind-1. Temperature at 23oC showed high SGR at 19% and clearance rate at 2.4x103 cells mL-1 ind-1 which was lower than salinity treatment. It shows that clearance rate affected more on change in temperature compared to salinity where spat tend to close valves as it reduced in filtering algal cells and yet decrease in spat growth. No mortality were observed. This study showed maturated oysters able to be found every month although during rainy season for hatchery spawning. Development of planktonic stage successfully recorded and C. iredalei is considered as a fast-grower bivalve. Used of bacteria biofilm identified as B. cereus promoted higher settlement and metamorphosis rate on larvae. Spat at size 6-7 mm were recommended for grow-out culture as it able to tolerate at broad range of salinity and temperature.